Given the following system of equations:
![\begin{cases}-3x-2y=-5 \\ 7x+y=1\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/ge6ms1b2jzx2lr4v0repzf18rzrse2quoj.png)
notice that we can multiply by 2 the second equation to get:
![2\cdot(7x+y=1)=14x+2y=2](https://img.qammunity.org/2023/formulas/mathematics/college/an0tp5ujnj67q474cb57eh5xgajibq6iy8.png)
then, we can add both equations to get the following:
![\begin{gathered} 14x+2y=2 \\ -3x-2y=-5 \\ ---------- \\ 11x=-3 \\ \Rightarrow x=-(3)/(11) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u93dqh16bu54l6sl6zl70yfh2wisw1ocv3.png)
Now that we have that x=-3/11, we can use this value to find y on the original second equation:
![\begin{gathered} 7(-(3)/(11))+y=1 \\ \Rightarrow-(21)/(11)+y=1 \\ \Rightarrow y=1+(21)/(11)=(11)/(11)+(21)/(11)=(32)/(11) \\ y=(32)/(11) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8hjy0nsslnh05wn6n57fl5phkodh87ni3x.png)
therefore, the solution of the syste is (-3/11,32/11)